2006
DOI: 10.1007/s10549-006-9245-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of eNOS, Hormone Receptor Status, and Survival of Breast Cancer

Abstract: The endothelial cell-specific form of nitric oxide synthase (eNOS) may play an important role in tumor progression via angiogenesis or apoptosis. We studied eNOS -786T > C and 894G > T (Glu298Asp), two functionally significant SNPs, in relation to hazard of breast cancer recurrence or death in 873 women with incident, non-metastatic breast cancer, recruited from two teaching hospitals in Seoul, Korea, 1995-2002. Hazards were estimated by Cox proportional hazard models, in relation to genotype, adjusting for ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 19 publications
3
31
0
Order By: Relevance
“…Notably, low eNOS immunohistochemical expression has been found to be associated with adverse prognostic features (23) and poor survival (24). Moreover, Choi et al reported poor survival in breast cancer patients bearing polymorphisms associated with low eNOS activity (25,26). Also, as in our study (trend for significance shown in Table III), other investigators (23,27) found higher eNOS mRNA expression in hormone receptorpositive tumors.…”
Section: Patients ---------------------------------------------------supporting
confidence: 85%
“…Notably, low eNOS immunohistochemical expression has been found to be associated with adverse prognostic features (23) and poor survival (24). Moreover, Choi et al reported poor survival in breast cancer patients bearing polymorphisms associated with low eNOS activity (25,26). Also, as in our study (trend for significance shown in Table III), other investigators (23,27) found higher eNOS mRNA expression in hormone receptorpositive tumors.…”
Section: Patients ---------------------------------------------------supporting
confidence: 85%
“…Genetic comparison studies on healthy people and cancer victims have shown that gene polymorphisms in eNOS are associated with the development of multiple cancers (15,16). Although the functional effect of eNOS polymorphisms has yet to be determined, these data support the hypothesis that an abnormal eNOS gene might drive tumorigenesis in humans.…”
Section: Cancer Researchmentioning
confidence: 56%
“…Myeloperoxidase (MPO) and endothelial nitric oxide synthase (eNOS) generate ROS, and polymorphisms resulting in reduced expression of these enzymes have been linked to poorer breast cancer survival. 21,22 Manganese superoxide dismutase (MnSOD), catalase (CAT) and glutathione-S-transferases (GSTs) are involved in pathways that neutralize ROS, and genotypes associated with higher levels of oxidative stress have been associated with better breast cancer survival. 21,23,24 Although higher levels of ROS may result in better tumor cell kill and thus, better survival, genetic variants that result in generation of ROS may also predispose to higher risk of skin toxicities.…”
mentioning
confidence: 99%